Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Let's evaluate the given piecewise function [tex]\( f(x) = \left\{\begin{array}{ll} -\frac{1}{2} x^2 + 5 & \text{if } x \neq 2 \\ 1 & \text{if } x = 2 \end{array}\right. \)[/tex] at the points [tex]\( x = -1 \)[/tex], [tex]\( x = 2 \)[/tex], and [tex]\( x = 5 \)[/tex].
### 1. Finding [tex]\( f(-1) \)[/tex]:
Since [tex]\( -1 \neq 2 \)[/tex], we use the formula [tex]\( f(x) = -\frac{1}{2} x^2 + 5 \)[/tex].
Substitute [tex]\( x = -1 \)[/tex] into the formula:
[tex]\[ f(-1) = -\frac{1}{2} (-1)^2 + 5 \][/tex]
Calculate [tex]\((-1)^2\)[/tex]:
[tex]\[ (-1)^2 = 1 \][/tex]
Multiply by [tex]\(-\frac{1}{2}\)[/tex]:
[tex]\[ -\frac{1}{2} \cdot 1 = -\frac{1}{2} \][/tex]
Add 5:
[tex]\[ -\frac{1}{2} + 5 = 4.5 \][/tex]
So, [tex]\( f(-1) = 4.5 \)[/tex].
### 2. Finding [tex]\( f(2) \)[/tex]:
Since [tex]\( 2 = 2 \)[/tex], we use the specific value given by the piecewise function for [tex]\( x = 2 \)[/tex]:
[tex]\[ f(2) = 1 \][/tex]
### 3. Finding [tex]\( f(5) \)[/tex]:
Since [tex]\( 5 \neq 2 \)[/tex], we use the formula [tex]\( f(x) = -\frac{1}{2} x^2 + 5 \)[/tex].
Substitute [tex]\( x = 5 \)[/tex] into the formula:
[tex]\[ f(5) = -\frac{1}{2} (5)^2 + 5 \][/tex]
Calculate [tex]\( (5)^2 \)[/tex]:
[tex]\[ (5)^2 = 25 \][/tex]
Multiply by [tex]\(-\frac{1}{2}\)[/tex]:
[tex]\[ -\frac{1}{2} \cdot 25 = -12.5 \][/tex]
Add 5:
[tex]\[ -12.5 + 5 = -7.5 \][/tex]
So, [tex]\( f(5) = -7.5 \)[/tex].
### Summary of Results:
[tex]\[ f(-1) = 4.5 \][/tex]
[tex]\[ f(2) = 1 \][/tex]
[tex]\[ f(5) = -7.5 \][/tex]
Thus, we have found that [tex]\( f(-1) = 4.5 \)[/tex], [tex]\( f(2) = 1 \)[/tex], and [tex]\( f(5) = -7.5 \)[/tex].
### 1. Finding [tex]\( f(-1) \)[/tex]:
Since [tex]\( -1 \neq 2 \)[/tex], we use the formula [tex]\( f(x) = -\frac{1}{2} x^2 + 5 \)[/tex].
Substitute [tex]\( x = -1 \)[/tex] into the formula:
[tex]\[ f(-1) = -\frac{1}{2} (-1)^2 + 5 \][/tex]
Calculate [tex]\((-1)^2\)[/tex]:
[tex]\[ (-1)^2 = 1 \][/tex]
Multiply by [tex]\(-\frac{1}{2}\)[/tex]:
[tex]\[ -\frac{1}{2} \cdot 1 = -\frac{1}{2} \][/tex]
Add 5:
[tex]\[ -\frac{1}{2} + 5 = 4.5 \][/tex]
So, [tex]\( f(-1) = 4.5 \)[/tex].
### 2. Finding [tex]\( f(2) \)[/tex]:
Since [tex]\( 2 = 2 \)[/tex], we use the specific value given by the piecewise function for [tex]\( x = 2 \)[/tex]:
[tex]\[ f(2) = 1 \][/tex]
### 3. Finding [tex]\( f(5) \)[/tex]:
Since [tex]\( 5 \neq 2 \)[/tex], we use the formula [tex]\( f(x) = -\frac{1}{2} x^2 + 5 \)[/tex].
Substitute [tex]\( x = 5 \)[/tex] into the formula:
[tex]\[ f(5) = -\frac{1}{2} (5)^2 + 5 \][/tex]
Calculate [tex]\( (5)^2 \)[/tex]:
[tex]\[ (5)^2 = 25 \][/tex]
Multiply by [tex]\(-\frac{1}{2}\)[/tex]:
[tex]\[ -\frac{1}{2} \cdot 25 = -12.5 \][/tex]
Add 5:
[tex]\[ -12.5 + 5 = -7.5 \][/tex]
So, [tex]\( f(5) = -7.5 \)[/tex].
### Summary of Results:
[tex]\[ f(-1) = 4.5 \][/tex]
[tex]\[ f(2) = 1 \][/tex]
[tex]\[ f(5) = -7.5 \][/tex]
Thus, we have found that [tex]\( f(-1) = 4.5 \)[/tex], [tex]\( f(2) = 1 \)[/tex], and [tex]\( f(5) = -7.5 \)[/tex].
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.